2020
DOI: 10.1001/jama.2020.4812
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Blockers

Abstract: This Viewpoint reviews the pathophysiological and observational basis for speculating that angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) might worsen clinical outcomes for patients with COVID-19, and summarizes guidance from specialty societies to continue the drugs in patients who need them pending more definitive evidence of harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
382
1
27

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(415 citation statements)
references
References 7 publications
5
382
1
27
Order By: Relevance
“…ACE inhibitors are commonly used in COVID-19 patients with comorbidities of hypertension, diabetes mellitus, and coronary heart diseases (Fang et al, 2020, Ferrario et al, 2005, indicating to physicians that patients on these medications may be more susceptible to SARS-CoV-2 infection. Indeed, since epidemiological studies have reported increased mortality and morbidity in COVID-19 patients with hypertension, more research needs to be done to address other confounding variables including other comorbidities and treatment with ACE inhibitors or angiotensin receptor blockers (Patel and Verma, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…ACE inhibitors are commonly used in COVID-19 patients with comorbidities of hypertension, diabetes mellitus, and coronary heart diseases (Fang et al, 2020, Ferrario et al, 2005, indicating to physicians that patients on these medications may be more susceptible to SARS-CoV-2 infection. Indeed, since epidemiological studies have reported increased mortality and morbidity in COVID-19 patients with hypertension, more research needs to be done to address other confounding variables including other comorbidities and treatment with ACE inhibitors or angiotensin receptor blockers (Patel and Verma, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB) are apparently required for the normalization of the abnormally high level of Angiotensin II patients with COVID-19 [9]. However, no consensus has yet been reached about the use of ACEI and ARB in patients with COVID-19 [34]. The other challenge is that whereas the 2019-nCoV is isolated from the host and grown in host cells, there is no animal model of disease to judge the condition is caused by 2019-nCoV [35].…”
Section: Expert Opinionmentioning
confidence: 99%
“…4,15,16 The role of ACEI and ARB in COVID-19 infection remains controversial -as the data is not adjusted for confounding factors of age and other comorbidities to definitively show that ACEI or ARB are independently associated with worse outcomes -and of course, this does not show causality either. 17 Hence, various independent medical societies have put out position statements that recognize the potential risks but given the current quality of evidence, recommend against inappropriate cessation or switch from ACEI/ARB therapy for hypertension, given its proven benefits. 18,19 Therefore, the objective of this study was to investigate the role of several adjuvant treatments in preventing severe pneumonia in COVID-19 patients from seven cities in Hunan province, China.…”
Section: Introductionmentioning
confidence: 99%